The Effect of an Effective Coping Styles Training Program on Coping Strategies for Stress in Nurses Working in Clinical Departments Dealing with COVID-19 in Iran - Sima Ghezelbash; Soheila Bakhtiari; Saeid Amini Rarani (Mashhad University of Medical Sciences, 2024)
Background: The prevalence of COVID-19 has caused stress, especially among nurses. On the other hand, the use of effective coping styles during the COVID crisis reduces stress in individuals.Aim: The present study was conducted with aim to investigate the effect of coping styles training program on coping strategies for stress in nurses.Method: This experimental study was conducted on nurses working in COVID-19 departments in April 2021. After obtaining informed consent, 80 participants were randomly divided into intervention and control groups. In the intervention group, training sessions were held as webinars for 3 sessions, each lasting 2 hours over three weeks. The Stress Coping Styles Questionnaire designed by Endler and Parker was completed by participants before and after the intervention. Data were analyzed by SPSS software (version 16) and one-way analysis of variance and paired t-test. p<0.05 was considered statistically significant.Results: After implementing the intervention, problem-focused coping styles increased among nurses working in COVID departments, while emotion-focused and avoidance-focused coping styles decreased after training sessions.Implications for Practice: Training the stress coping methods can lead to effective use of coping styles during crises such as COVID-19 among nurses working in COVID departments.